2018
DOI: 10.1159/000493945
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes Mellitus among Hepatitis C Virus-Infected Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The ever-increasing global prevalence of hepatitis C infection is fueling the burden of diabetes mellitus, which exacerbates various complications and may be a cause of death of millions of people. Several studies have reported that hepatitis C virus infection is an important risk factor for the development of diabetes mellitus. However, fragmented studies have reported variable and inconsistent findings regarding the prevalence of type 2 diabetes mellitus among hepatitis C virus-infected patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The high CVD risk in NAFLD patients with MetS could be due to an increase in fibrosis stage, steatosis grade, or oxidative stress [86], which are collectively induced by FFAs. HCV infection has similarly been identified as a potential risk factor for both T2DM-and CVD-related complications [87,88]. HCV core protein upregulates TNF-α and SOCS3, causing the phosphorylation and ubiquitination of IRS-1/IRS-2, respectively, preventing it from associating with the insulin receptor and further blocking the activation of AKT.…”
Section: Hcv-related Steatosis and Extrahepatic Manifestationsmentioning
confidence: 99%
“…The high CVD risk in NAFLD patients with MetS could be due to an increase in fibrosis stage, steatosis grade, or oxidative stress [86], which are collectively induced by FFAs. HCV infection has similarly been identified as a potential risk factor for both T2DM-and CVD-related complications [87,88]. HCV core protein upregulates TNF-α and SOCS3, causing the phosphorylation and ubiquitination of IRS-1/IRS-2, respectively, preventing it from associating with the insulin receptor and further blocking the activation of AKT.…”
Section: Hcv-related Steatosis and Extrahepatic Manifestationsmentioning
confidence: 99%
“…Hepatocytes are crucial for maintaining plasma glucose homeostasis; the main objective of our study was to investigate the impact of DAAs treatment and viral clearance on the metabolic profile in treated patients. Our findings in relation to the prevalence of dysglycemia in patients beginning therapy were high, when compared to most of the literature, being 43.8% pre-diabetic, against 12.5% diabetic, mainly due to stratification criteria; in one of the largest published reviews on the subject, with 62,354 patients, Ioannou et al (27) found 22.0% of patients diagnosed with diabetes; similarly, in a meta-analysis carried out in 2018 by Ambachew et al (29), involving 14,765 patients, the prevalence of DM2 among those infected with HCV was 19.6%. With a broader scope in the classification of patients, between pre-diabetes and diabetes, Yuan et al (30) found findings of 25.5% for pre-diabetes and 8.16% for DM2; similarly, in the review by Weidner et al (23), 27.0% of patients had changes in glycemic homeostasis at baseline, and obtained a reduction in fasting plasma glucose levels and HbA1c values independent of changes in BMI with therapy with DAAs.…”
Section: Discussionmentioning
confidence: 90%
“…20 One more systematic Review meta-analysis reported that 19.67% of HCV infection cases had DM. 21 Riaz S, et al 22 observed that type II DM was 27% among chronic HCV infected patients. Allison et al reported that among cirrhosis patients who were looking forward for transplantation, HCV infected patients were 5 folds more expected to have T2DM as compared to those who did not have HCV, irrespective of sex, severity of hepatic disease or BMI.…”
Section: Resultsmentioning
confidence: 97%